THE IMPACT OF INTERNET DISTRIBUTION SYSTEMS ON PROMOTION, SALES AND QUALITY OF HOTEL ACCOMMODATION (WITH 4 AND 5 STARS IN A CITY OF NIŠ): 1.Use of modern information technology in hospitality - Stanković, Tamara; Čerović, Slobodan (Turističko poslovanje, 2021)
The abstract:This work is theoretical and empiric review of influence of IDS and social networks on promotion, sales and quality of hotel accommodation. The work shows theoretical-academic presentation and it includes a case study, which was made by research in hotels with 4 and 5 stars. The research identifies the usage and influence of IDS on promotion, sales and quality of hotel accommodation, key advantages and deficiency of cooperation, as well as the usage and importance of social networks in promotion and sales. The importance, definition and term of IDS and social networks in hotel businesses are shown in theoretical part of this work. The main point of this work is to prove the importance of impact of application IDS and social networks on promotion, sales and quality of accommodation, to show advantages and disadvantages of cooperation, as well as the importance of monitoring and harmonization of hotels with innovations, their usage, harmonization of an offer with demand on market.
Keywords: Internet distribution systems; social networks; promotion; sales; quality